Consumption Risk Sharing over the Business Cycle: The Role of Small Firms' Access to Credit Markets - Hoffmann, Mathias; Shcherbakova-Stewen, Iryna (The Review of Economics and Statistics, 2011)
Consumption risk sharing among U.S. states increases in booms and decreases in recessions. These business cycle fluctuations in interstate risk sharing are driven mainly by states in which small businesses account for a large share of income or employment. State-level banking deregulation during the 1980s loosened the dependence of interstate risk sharing on the business cycle, mainly through its impact on states with many small firms. Our results establish a major benefit from bank deregulation: small firms' access to credit and, with it, interstate risk sharing have improved mainly when it is most urgently needed: in nationwide economic downturns.